2018
DOI: 10.20472/te.2018.6.1.007
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Gap in Math. Evidences of a Study in the Primary School in the Swiss Canton of Ticino

Abstract: This work analyzes the gender gap in math results of an entire cohort of students attending the fifth grade of the primary school in the Swiss canton of Ticino. Three evaluation contexts have been considered: the mark itself assigned by the teacher at the end of the school year, the score obtained in a standardised math test and the evaluation provided by teachers in the same school year. Multivariate analysis allows to conclude that all things being equal, gender plays a significant effect on the mark in math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
2
0
0
Order By: Relevance
“…Also, the original study found CRT is gender sensitive, the number of male participants with CRT high scores was significant higher comparing to the number of female participants. These results are consistent with those of Zanolla (2018), who concluded that males are more likely than females to achieve a high mark at math tests and they are perceived as more active and participative, while females are seen as more conform to school rules, but less involved and more insecured. 3…”
Section: Introducing Crtsupporting
confidence: 91%
“…Also, the original study found CRT is gender sensitive, the number of male participants with CRT high scores was significant higher comparing to the number of female participants. These results are consistent with those of Zanolla (2018), who concluded that males are more likely than females to achieve a high mark at math tests and they are perceived as more active and participative, while females are seen as more conform to school rules, but less involved and more insecured. 3…”
Section: Introducing Crtsupporting
confidence: 91%
“…For University, the results are in line with the previous studies, the short CRT score is 0.63 and compared to the lowest University score in the original study, the percents for the extremes are better and the intermediate ones are worse. The boys outperformed the girls, 0.8 compared to 0.58, sustaining the previous studies (Zanolla, 2018). 8 But for secondary school and for high school, the results are different, in both cases the girls significantly outperformed the boys and this result stands included for all girls and all boys.…”
Section: Research Hypothesissupporting
confidence: 85%